REGRESSION ANALYSIS FOR THE DYNAMIC RESPONSES OF SEMI-SUBMERSIBLE PLATFORM - Ng , C.Y. (2011)
Semi-submersible is a type of offshore floating platform that is made up of large-sized vertical hulls and horizontal pontoons for providing buoyancy. The wave diffraction theory is the proper theory to be applied for the calculation of wave forces and wave damping for large structures such as semi-submersible platforms. A validation work was performed where the responses in term of response amplitude operators (RAOs) considering diffraction theory were obtained by using the linear wave diffraction analysis. In this work, a scale model was fabricated and tested in the wave tank of the offshore engineering laboratory of Universiti Teknologi PETRONAS. Regular waves of various applicable frequencies were used for the tests. The analytical responses were compared with the measured responses of the model tests. The applicability of diffraction theory for such platform was justified by the good comparisons obtained. By using the results of the linear wave diffraction analysis for a large number of platforms, a simpler approach to obtain the diffraction responses, the non-linear multiple regression analysis, was introduced. In this paper, a series of formulae for regression curves to predict the diffraction responses of the semi-submersible platforms for any dimension and draft within the suggested range are presented.